Use of barbed suture for peritoneal closure in transabdominal preperitoneal hernia repair - Takayama, Satoru (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate the use of the V-Loc wound closure device for transabdominal preperitoneal hernia repair. METHODS: We performed conventional transabdominal preperitoneal hernia repair in 19 patients, including one single incisional case using V-Loc. Except for the use of V-Loc for peritoneal closure, the procedures were the same as those used in conventional techniques. RESULTS: Although the operators included 2 residents who have no experience in laparoscopic herniorrhaphy and intracorporeal suture, the operations were completed. We believe that V-Loc is especially suitable for inexperienced surgeons and the use of V-Loc reduces the operative time by a small amount but reduces operator stress significantly. CONCLUSION: We conclude that V-Loc is the ideal peritoneal closure device for transabdominal preperitoneal hernia repair.